André Schroeder (1918-2004) - Groundbreaking Pioneer in Swiss Academic Dentistry : on the occasion of the anniversary of the long-standing Editor of the "Schweizer Monatsschrift für Zahnheilkunde" - Reinecke, Katharina (Swiss dental journal, 2019)
The career of André Schroeder (1918–2004), Professor of Operative Dentistry and Endodontics at the University of Bern, and long-term Editor in Chief of the Schweizerische Monatsschrift für Zahnheilkunde (predecessor of the Swiss Dental Journal SSO), is unique in many respects. Forty years ago, in 1979, Schroeder reached the zenith of his career when he was elected President (Rector) of the University of Bern – thereby becoming the first dentist in Swiss academic history to hold this office. Previously, Schroeder had also been the first dentist to become Full Professor (Ordinarius) and, later, Dean of the Medical Faculty. At the same time, Schroeder founded the International Team of Implantology (ITI), which evolved into the largest global organization of Implant Dentistry. The present article uses these anniversaries as an opportunity to (1) retrace Schroeder’s career path, (2) contextualize this career path using the education policy in place at the time, and (3) clarify to what extent and by which means the pioneer Schroeder influenced the professionalization of Academic Dentistry in Switzerland. This study draws upon primary sources from the University and City Archives of Bern and the archive of the ITI; these were supplemented by relevant secondary literature. An evaluation of the sources clearly shows that Schroeder was a trailblazer in many ways: Firstly, he exploited his university positions with the primary goal of furthering the basis of Academic Dentistry. Secondly, he promoted Swiss Dentistry through his non-university activities – as the successful Editor of the Schweizerische Monatsschrift fu?r Zahnheilkunde and founder of the ITI. And thirdly, Schroeder specifically addressed the increasing relevance of Dentistry for society as a whole by intertwining the two most important arguments – the scientific orientation and the benefits for public health – in a rhetorically accomplished manner.